Paleonura bilinskii (Collembola, Neanuridae, Paleonurini), a new species from Ecuador - Paśnik, Grzegorz; Weiner, Wanda Maria (Zootaxa, 2013)
The genus Paleonura Cassagnau, 1982, with 50 species, is found mainly in the tropical and subtropical regions of the world with some species restricted to high altitudes. Eighteen species have been described from the mountains above 800 m a. s. l., in the Himalayas (13 species) and Kenya and Tanzania (three species each). Seven species (together with the new one) have been found in the mountains above 3000 m a. s. l.: P. ganesh Cassagnau, 1991, P. indrabahadouri Cassagnau, 1991, P. setikholensis Cassagnau, 1991, P. spectabilis Cassagnau, 1982, P. khumbica Yosii, 1971 (all Himalayas), P. africana Cassagnau, 1996 (Kenya) and P. bilinskii sp. nov. (Ecuador). The northernmost record of the genus is P. peterbellingeri Palacios-Vargas & Simón Benito, 2007, from a cave in Virginia, USA (38°55'59.44" N) and the most southern, P. limnophila (Cassagnau & Rapoport, 1962) from Argentina (42°52'24.48" S).